Construction of spiritual meaning in the transformation of gratitude for freshmen - Rizky Andana Pohan; M. Ramli; Adi Atmoko; Sa'dun Akbar (HTS Teologiese Studies/Theological Studies)
This study explores the dynamics of emotional expression of freshmen students at a public university in Indonesia, focussing on the role of gratitude in helping them overcome challenges and maintain academic vigour. Using qualitative methods with open-ended questionnaires and in-depth interviews, this study involved 20 freshmen from one public university. The results showed that the majority of students expressed gratitude to God as the main expression, while a minority also valued the role of social support and personal achievement. The findings also revealed that despite uncertainties, fears and disappointments, gratitude remains a fundamental and culminating emotion. Gratitude not only helps students overcome challenges but also enhances their resilience and motivation. Spiritual Meaning Construction Theory serves as an analytical tool, highlighting that spiritual experiences and expressions of gratitude are strongly influenced by an individual’s social and cultural context. The theory emphasises that the experience of religion or spirituality has no universal truth, but rather varies according to each individual’s interpretative framework. The findings suggest that the expression of gratitude in freshmen not only reflects universally inculcated spiritual beliefs but is also a result of the meaning-making processes by individuals within their social and cultural context. Implications for higher education institutions include the importance of developing orientation, counselling and academic support programmes that support students’ expression of gratitude and resilience. Programmes that promote resilience and gratitude can help students overcome challenges and stay motivated throughout their academic journey.